Strategie kształcenia interkulturowych kompetencji menedżerskich - Słabicka, Małgorzata (Intercultural Education for Managers, 2008)
Efficiency of international business activities is strongly related to flexibility and adaptive skill of managers in dealing with foreign cultures. It is therefore important to provide managerial staff with suitable training of intercultural competence. The paper presents selected strategies for training managers to deal with variety of cultural contexts. Those methods are based on integration of intercultural dements into academic-level studies and inservice training, in the form of workshops, lectures, training and education using multimedia and online resources.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 216-222